Carrying capacity in short bit-string penna model - Piñol, Chrysline Margus Nonga
We investigate the need for imposing the concept of a carrying capacity (Verhulst factor) in short bit-string Penna model. The main motivation for its introduction is to make certain that the simulated population is kept finite. This was done by evaluating the fractional contribution of each death factor to the total number of deaths in the population. The effect of the verhulst factor was observed to diminish with increasing minimum reproductive age compared to other death factors. We find that within the framework of the Penna model, there are cases for which the concept is unnecessary to keep the population finite. Populations for which the carrying capacity is not required to prevent unlimited growth were identified. These were observed to have zero steady states. A stable population without imposing the Verhulst factor was obtained only when the birth rate B = 1, the mutation threshold T = Tmax = NG and the mimimum reproductive age R = Rmax = ( NG - 1 ) where NG i s the bit-string length. Furthermore, we present an alternative implementation of the model removing random deaths caused by the verhulst factor. The stable populations obtained for the implementation with dynamically changing mimimum reproductive age yielded a time-varying R-distribution. Obtaining parameters that yield a stable, nonzero population with a time-independent R-distribution proved elusive as of the time of the writing. PACS: 87.23.-n [Ecology and evolution], 87.10.+e [General theory and mathematical aspects], 07.05.Tp [Computer modelling and simulation], 02.70.-c [Computational techniques